Differences between Members and Shareholders of a Friendly Society and the Payment of Dividends: A South African–Australian Perspective - Neels Kilian (Potchefstroom Electronic Law Journal, 2021)
This article focusses on a very specific problem statement, namely how shareholder society relationships are viewed in Australia and South Africa. Friendly societies are special "legal creatures" enjoying legal personality from the date and time of their registration (not as companies). In South Africa friendly societies have been in existence for more than 160 years, with the latest legislation being promulgated in 1956. As an unregistered company, the friendly society forms part of the South African business enterprise landscape and has both members and shareholders. The legal relationships between members and shareholders and the payment of a dividend are unclear in the Friendly Society Act, 1956, and are generally regulated by the constitution or memorandum of incorporation of the friendly society. In Australia friendly societies developed approximately 200 years ago. In 1999 friendly society legislation was repealed by the Financial Sector Reform Act, 1999, in terms of which friendly societies had to convert to companies either as companies limited by guarantee or public companies as regulated by the Corporations Act, 2001. Prior to 1999, friendly societies were largely regulated by the Queensland Friendly Society Act, 1997 as unregistered companies. The Code regulated the relationships between members and shareholders and the payment of dividends. In this article we also focus on Australian friendly societies after 1999 and how they compare with South African friendly societies with regard to the member/shareholder relationships and the payment of dividends.